Effect of Capital Investment on The Level of Internationalization of Companies in ASEAN-5 Period 2009-2018 - Jessica Chandra Chairunnisa; Liyu Adhi Kasari Sulung; Kirana Rukmayuninda Ririh (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
This study aims to determine the effect of capital investment on the level of internationalization and to see the effect of a larger capital investment and a larger company size on the relationship between the two of them in companies in Indonesia, Malaysia, the Philippines, Thailand and Singapore. This study uses the Generalized Least Square (GLS) balanced data panel method with annual data for the 2009-2018 period. The results of this study indicate that capital investment has a negative and significant influence on the level of internationalization. However, this study found that large capital investment moderates the effect of capital investment on the level of internationalization, so that the relationship between the two is nonlinear or U-shaped. This study also found that company size did not moderate the relationship between capital investment and the level of internationalization, so that the negative effect of capital investment on the level of internationalization did not differ in large companies.